Comparing three stages of addiction recovery: long-term recovery and its relation to housing problems, crime, occupation situation, and substance use. (2nd September 2020) - Martinelli, Thomas F.; Nagelhout, Gera E.; Bellaert, Lore; Best, David; Vanderplasschen, Wouter; van de Mheen, Dike
Abstract: Many studies on addiction recovery focus on recovery initiation and short-term outcomes for alcohol addictions. In this study, we examine associations between three recovery stages and recovery markers for persons in drug addiction recovery. Data were collected for a multi-country study (REC-PATH) among 722 individuals living in the UK, the Netherlands, and Belgium, who consider themselves in addiction recovery for a period of three months or more. We focus on typical life domains that characterize recovery: housing, crime, work or education, and substance use. The relation with time in recovery was examined for three recovery stages: early (<1 year), sustained (1–5 years), and stable (>5 years). Using the Life in Recovery survey, cross-sectional analyses reveal that participants in later recovery stages have lower odds of having housing problems, being involved in crime, and using illicit hard drugs and higher odds of having work or education, when compared to participants in the early recovery stage. This study provides further empirical support for defining drug addiction recovery as a gradual, long-term process that is associated with various life domains beyond abstinence. The findings suggest that drug policy, treatment and research need to be oriented towards long-term objectives and recovery goals that cover multiple life domains in order to support stable recovery.